TAXATION AND ECONOMIC GROWTH IN NIGERIA - Gbenga, Oyegun; Nicholas, Efangwu Ugochukwu (Research Parks Publishers, 2023)
The pivotal role of taxation in revenue generation cannot be under emphasis in any economy. Due to its importance, this study has been carried out to investigate the impact of taxation on economic growth in Nigeria. Four hypotheses were stated and tested. The study used mostly secondary data from the Central Bank of Nigeria Bulletin (CBN) and reports from Federal Inland Revenue for the period of 29 years (1994 – 2022). The study used Regression Analysis by applying an Error Correction Model (ECM) and Granger Causality Approach based on the outcome of the unit root test and to discover both long and short run effect. The study revealed that Custom and Excise Duty has a negative and insignificant impact on Nigeria Gross Domestic Product in the short run. Petroleum Profit Tax (PPT) has a negative impact on the Nigeria Gross Domestic Product in the short run. However, Value Added Tax (VAT) and Company Income Tax both have positive and significant impact on Nigeria Gross Domestic Product in the short run. The study recommended that Efforts should be intensified by the government towards increased collection of tax revenue this is due to the low contribution of tax revenue to GDP over the period of study. This can be done through blocking all loopholes in our tax laws as well as bringing more prospective tax payers into the tax net (especially the informal sector). Also there should be stringent penalty imposed on any individual or corporate body who indulge in any form of tax malpractices, if the positive correlation between taxation and economic growth should be maintained.